2019
DOI: 10.1002/ijop.12538
|View full text |Cite
|
Sign up to set email alerts
|

Zero‐sum thinking as mediator of the relationship of national attitudes with (un)willingness to host refugees in own country

Abstract: This study examines factors related to willingness to host refugees. We examined the role of national attitudes (patriotism, nationalism), out‐group attitudes (classic and modern prejudice), and zero‐sum thinking: Belief in a Zero‐Sum Game and psychological entitlement in attitudes towards hosting refugees. We proposed including zero‐sum thinking as possible mediator between national attitudes and attitudes towards refugees based on assumption that nationalism is a competitive attitude towards out‐groups, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
(61 reference statements)
2
14
0
1
Order By: Relevance
“…However, the collective narcissism levels remain unchanged in Poland (www.pandemic .monitor). Moreover, the main findings are congruent with the studies conducted before the pandemic (Deslandes & Anderson, 2019;Piotrowski et al, 2019;Whitley, 2009;Żemojtel-Piotrowska et al, 2020), and statistically controlling for fears of COVID-19 did not change the main results. 5 The Polish cultural context could affect the strength of the relationship between national narcissism and religiosity because Poland is a highly religious country (Boguszewski et al, 2020).…”
Section: Refugees and Sexual Minorities In Polandsupporting
confidence: 85%
See 1 more Smart Citation
“…However, the collective narcissism levels remain unchanged in Poland (www.pandemic .monitor). Moreover, the main findings are congruent with the studies conducted before the pandemic (Deslandes & Anderson, 2019;Piotrowski et al, 2019;Whitley, 2009;Żemojtel-Piotrowska et al, 2020), and statistically controlling for fears of COVID-19 did not change the main results. 5 The Polish cultural context could affect the strength of the relationship between national narcissism and religiosity because Poland is a highly religious country (Boguszewski et al, 2020).…”
Section: Refugees and Sexual Minorities In Polandsupporting
confidence: 85%
“…REFUGEES AND SEXUAL MINORITIES IN POLAND 3 attention in the context of studies on prejudice and religion, as they represent a threat to those values which are essential for religious individuals (Deslandes & Anderson, 2019;Whitley, 2009), but refugees are also seen as a realistic threat because they may be perceived as competing for economic resources (Landman et al, 2019;Piotrowski et al, 2019). Spirituality is associated with more openness to others (Piotrowski & Żemojtel-Piotrowska, 2020a) and less of a SDO (Hirsh et al, 2013;Lockhart et al, 2020), so this kind of worldview could explain their lower prejudice toward those groups which are threatening for highly religious people.…”
Section: The Present Studymentioning
confidence: 99%
“…For individuals scoring low in nationalism, national values are less relevant to define their self-concept (Roccas, Klar & Liviatan, 2006), so the involvement in a competitive situation is more likely to lead to outgroup prejudice than flag exposure because of the lack of centrality of national values associated with egalitarianism and inclusiveness. Consistent with this idea, Piotrowski et al (2019) found that different forms of national identification predicted prejudice toward refugees when they were associated with zero-sum thinking.…”
Section: The Moderator Role Of Nationalismmentioning
confidence: 66%
“…Under these zero-sum situations, intergroup conflict and prejudice are likely to arise (Huddy, 2003). In such a context, making salient the national ingroup should result in outgroup prejudice (Piotrowski et al, 2019). On the other hand, previous studies have shown that flag exposure led to less outgroup prejudice among highly nationalistic individuals (Butz, Plant, & Doerr, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…The violence the lead author either witnessed or faced varied from derogatory language, bullying, altercations, and physical violence that even ended in death. While some scholars credit these acts of violence to the prejudice toward refugees which is still widespread among individuals and nations (Piotrowski et al 2019), some attribute the lack of social rest to the competition for resources and the unequal distribution of these resources (Schmidt et al 2015). Kebribeyah's case illustrates the evidence for the competition for limited and unequally distributed resources, most importantly education.…”
Section: Discussionmentioning
confidence: 99%